2021
DOI: 10.3201/eid2707.204593
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of Oseltamivir-Resistant and Hemagglutinin Antigenically Drifted Influenza A(H1N1)pdm09 Viruses, Texas, USA, January 2020

Abstract: R esistance to antiviral drugs for infl uenza is an ongoing public health concern. The neuraminidase (NA) inhibitor oseltamivir is the most prescribed antiviral drug for controlling infl uenza. However, during 2007-2009, oseltamivir-resistant infl uenza A(H1N1) viruses rapidly spread worldwide (1). Molecular mechanisms implicated in this event were acquisition of NA-permissive mutations that alleviated deleterious fi tness effects of the resistance-conferring mutation NA-H275Y (N1 numbering) (2); changes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The detection of A(H1N1)pdm09 viruses in untreated patients is an indicator of community transmission of resistant NA-H275Y viruses ( Hurt et al, 2012 ; Takashita et al, 2015b ), and this needs to be closely monitored. Notably, a small cluster of NA-H275Y viruses was detected in the United States in 2020 ( Mohan et al, 2021 ) and the antigenically drifted hemagglutinin of these viruses may facilitate their spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of A(H1N1)pdm09 viruses in untreated patients is an indicator of community transmission of resistant NA-H275Y viruses ( Hurt et al, 2012 ; Takashita et al, 2015b ), and this needs to be closely monitored. Notably, a small cluster of NA-H275Y viruses was detected in the United States in 2020 ( Mohan et al, 2021 ) and the antigenically drifted hemagglutinin of these viruses may facilitate their spread.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an increased frequency of A(H1N1)pdm09 viruses with potential RI/HRI in 2019–2020 (1.2%, 52/4195) was observed, compared to 2018–2019 (0.8%, 54/6765), based on analysis of sequences available in GISAID which matches frequencies of A(H1N1)pdm09 viruses analyzed by WHO CCs displaying RI/HRI (1.3% for 2019–2020 vs 0.7% for 2018–2019) ( section 2.2 .). Among these, three NA-H275Y viruses belonged to a cluster of oseltamivir-resistant viruses detected in the United States ( Mohan et al, 2021 ). Eight NA sequences had substitutions at residue 223 (NA-I223M/K/R/T), and three had NA-S247G substitutions.…”
Section: Neuraminidase Inhibitors (Nais)mentioning
confidence: 99%
“…Previous studies have also shown that both A(H1N1)pdm09 and A(H3N2) viruses with PA-I38T had good stability in ferret transmission studies 43,44 , but have shown limited person-to-person transmission 23,45 . Additionally, NA-H275Y stability has been demonstrated by widespread community transmission of the previous seasonal A(H1N1) virus in 2008-2009 8,9 and localised transmission in A(H1N1)pdm09 viruses [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in influenza viruses, like the most of RNA viruses, occur frequently due to the lack of viral RNA polymerase proofreading. These variations create mutants that are no longer preventive by vaccine ( 32 ). Therefore, antiviral medications can be of great importance in prophylaxis until new vaccine is available.…”
Section: Discussionmentioning
confidence: 99%